ANNUAL ENERGY BASED ON TIME SIMULATION OF MICROHYDRO POWER PLANT (PLTMH) JAMUS GIRIKERTO VILLAGE, SINE DISTRICT, NGAWI REGENCY - Rifqi, Muhammad Khoirur; Saves, Faradlillah; Patriadi, Andi (Jurnal Teknik Sipil, 2023)
PT. Candi Loka Jamus switched to using micro hydro power plants to meet its electrical energy needs because of the high operational costs and environmental impact of fuel oil power plants. However, during the dry season, the micro hydro power plant is unable to produce enough energy to meet the needs, which could lead to damage of its components and decreased performance. To address this issue, the energy potential of the micro hydro power plant was calculated using operational time simulation and season time simulation. The rain data was analysed using the double mass curve analysis method and arithmetic mean method to calculate the discharge throughout the year. The dependable discharge was calculated using the F.J. Mock method and the basic year method, and the physical potential formula was used to calculate the energy potential. Based on the calculations, the dependable discharge energy potentials of Q80, Q70, Q50, and Q30 were found to be 569,173.91 KWh, 614,737.01 KWh, 589,640.81 KWh, and 619,855.44 KWh, respectively. The efficient operating time of the micro hydro power plant was determined based on the Q80 dependable discharge energy potential with a simulation of operational time. The plant should be active from January 1 to August 15, deactivated for maintenance purposes from August 16 to October 31, and reactivated from November 1 to December 31. With an active period of 287 days, the Jamus micro hydro power plant has an energy potential of 488,732.17 KWh in one year.